Algunas reflexiones sobre los límites del oikoumene en el Imperio Romano - Hidalgo de la Vega, María José (Gerión. Revista de Historia Antigua, 2005)
This paper reflects on the Roman Empire as pattern of a world-wided politycal system former to the contemporary globalization. The analysis of this hegemonic order can help to understand rather our present.